ANALISIS FAKTOR-FAKTOR KEPUASAN KERJA PADA KARYAWAN PT. BANK TABUNGAN NEGARA KANTOR CABANG SOLO - Wardani, Maris Tri (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
The objectives of this research are to investigate: (1) whether or not there is a simultaneous and partial effect of the factors of salaries, employments, career promotions, supervisors, and co-workers on the work satisfaction with the financial compensation as the moderator variable; (2) which factors have the dominant effect on the the work satisfaction with the financial compensation as the moderator variable. This research used the quantitative descriptive research method. The samples of the research were all of the employeesasa many as 50 empployees. The data of the research were gathered through questionnaire and documentation. They were then analyzed by using the multiple regression analysis aided by the computer program of SPSS 17.The results of the research show there is a simultaneous effect of all the variables and not all of the variables have a partial effect on the work satisfaction with the financial compensation as the moderator variable. Variable of career promotions has the dominant effect on the work satisfaction with the financial compensation as the moderator variable.